IMPLEMENTASI HUKUM ATAS PENYALAHGUNAAN NARKOTIKA OLEH ANGGOTA KEPOLISIAN REPUBLIK INDONESIA BERDASARKAN UNDANG UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Bagus Ricky Pratama, Gede; Sudarto (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
The police as executors and law enforcers have the task of maintaining security within the Republic of Indonesia and are given the authority to prevent and eradicate criminal acts. The aim of this research is to examine and analyze law enforcement against police officers who commit criminal acts of narcotics abuse based on Law Number 35 of 2009 concerning Narcotics. This research is normative juridical research, using a statutory approach, conceptual approach and case approach. Regarding members of the police who commit narcotics abuse, these members of the National Police will file a case and undergo two types of judicial processes, namely general justice (the criminal justice process for members of the National Police of the Republic of Indonesia is generally carried out according to procedural law applicable in general courts). The second is disciplinary violators, and the third is disciplinary regulations. This disciplinary regulation is implemented when a court decision which has permanent legal force is then used as evidence to Propam regarding the violation committed. Based on Circular Letter Number: SE/9/V/2021 concerning Standard Guidelines for Implementing Violations of the POLRI Professional Code of Ethics, namely that drug abuse, including serious violations, can be recommended for Dishonorable Dismissal (PTDH), because drug violations are extraordinary criminal acts and constitute a common enemy that can damage the nation's generation and must be eradicated. Regarding members of the police who commit narcotics abuse, these members of the National Police will file a case and undergo two types of judicial processes, namely general justice (the criminal justice process for members of the National Police of the Republic of Indonesia is generally carried out according to procedural law applicable in general courts).